An engineering CFD model for fire spread on wood cribs for travelling fires. (November 2022) - Dai, Xu; Gamba, Antonio; Liu, Chang; Anderson, Johan; Charlier, Marion; Rush, David; Welch, Stephen
Highlights: An engineering CFD model for fire spread on wood cribs is demonstrated. Fire spread characterised at stick-by-stick level with at least 2 × 2 cells. Global matching of heat release rate, fire spread, burn-away and flame temperatures. Approximate linear regression between different fire modes and incident radiant heat fluxes. Heat release rate more sensitive to fire spread than stick burning rate. Abstract: The temperature heterogeneity due to fire in large open-plan office compartments is closely associated with fire spread behaviour and has been historically limited to experimental investigations using timber cribs. This study explores the ability of Computational Fluid Dynamics (CFD) models, specifically the Fire Dynamics Simulator (FDS), to reproduce the results of full-scale tests involving fire spread over timber cribs for continuous fuel-beds. Mesh schemes are studied, with a fine mesh over the crib and 2 × 2 cells in the wood stick cross-section by default, this being relaxed in the surrounding regions to enhance computational efficiency. The simple pyrolysis model considers the charring phase and moisture. In application to the TRAFIR-Liège LB7 test, this calibrated "stick-by-stick" representation shows a good agreement for interrelated parameters of heat release rate, fire spread, gas phase temperature, and burn-away, a set of agreements which has not been demonstrated in previous studies. Fire spread shows relatively high sensitivities to: heat of combustion, ignition temperature, thermal inertia, radiation fraction, heat release rate per unit area, and the fuel load density. An approximately linear regression was found between the different fire modes and the thermal exposures, with "travelling" (and decaying) fires characterised by heat fluxes associated with the fire plume, while the growing fires were associated with proportionally higher heat fluxes on the horizontal surfaces of the sticks, in conditions where these receive more pre-heating. The trends in the overall HRR are more dependent on the fire spread rates than variations in the stick burning rates.